Subcutaneous avulsion of the flexor digitorum profundus muscle - Tylla, A; Strube, T (Der Unfallchirurg, 2009)
The diagnostic and treatment of a closed avulsion of the flexor digitorum profundus muscle at its insertion of the little finger is presented. This happened as a 41-year-old woman wanted to hold a dog lead in her left hand and suddenly the dog started to run. In the literature the flexor digitorum profundus (FDP) and flexor pollicis longus (FPL) tendons were found to be more frequently ruptured than the flexor digitorum superficialis tendon. Closed ruptures of the FDP have been rarely reported. In the case described here there was no torn fragment at the distal end of the FDP tendon and the bone structure of the phalanx distales was intact. The operative treatment, postoperative care and clinical course are presented.